The Efficacy of the Merdeka Mengajar Platform on the Quality of Education at Torue State Senior High School - Exsa Putra; Widyastuti; Iwan Alim Saputra; Amalia Novarita; Rendra Zainal Maliki; Astri (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the role of the Merdeka Mengajar platform and learning facilities on the learning quality of 11th and 12th-grade students at SMAN 1 Torue. Based on the research results, the utilization of the Merdeka Mengajar platform falls into the “good” category with a mode of 67%, while the school’s learning facilities are also in the “good” category with a mode of 56%. The students’ learning quality in the studied subjects is similarly categorized as good, with a mode of 65%. According to the analysis, learning quality is substantially affected by the Merdeka Mengajar platform, contributing 24%, while school learning facilities contribute 20%. Furthermore, the Merdeka Mengajar platform and Students' learning quality is profoundly affected by learning facilities taken collectively, indicating a synergistic effect of these factors in enhancing learning effectiveness. These findings highlight the importance of utilizing educational technology and providing adequate learning facilities to assist in the implementation of the Merdeka Curriculum and improve student learning outcomes.